Prevalence of latent prostate cancer and prostatic intraepithelial neoplasia in Istanbul, Turkey: an autopsy study - Akpolat, Nusret; Buyuk, Yalcin; Uzun, Ibrahim; Gecit, Ilhan; Kurnaz, Gulay (Tubitak Scientific & Technological Research Council Turkey, 2012)
Aim: To investigate the frequency of latent prostatic carcinoma (PCa) and prostatic intraepithelial neoplasia (PIN) in the Turkish population. Materials and methods: PCa and PIN were evaluated in 116 male autopsy cases in which the cause of death was nontumoral. All patients were Turkish, living in Istanbul, and aged 40-79 years. Results: The prevalence of PCa was 19.8% and the decade rates (decades 5-8) were 9.5%, 12.5%, 18.8%, and 37%, respectively (P < 0.011). The rates of high-grade prostatic intraepithelial neoplasia (HGPIN) were 33.3%, 31.3%, 56.3%, and 25.9% for decades 5-8, respectively (P > 0.05). A total of 68.4% of PCa cases were HGPIN. There was a statistically significant correlation among HGPIN, PCa, and Gleason scores (P < 0.002). Conclusion: The prevalence of latent PCa in the Turkish population is very high (19.7%). In order to determine latent PCa cases, males over 40 years of age must be screened more strictly.
Türkiye, İstanbul'da latent prostat kanseri ve prostatik intraepitelyal neoplazinin sıklı?ı: Otopsi çalışması
Keywords: Prostate cancer; prostatic intraepithelial neoplasia; prevalence; Turkish males; autopsy